Classical and Modern Citizenship Concept in Islamic Perspective - Irfan, Try Wiganda (Journal of Moral and Civic Education, 2018)
There are two concepts of Islamic citizenships, the Muslims and dhimmi. The concept of dhimmi citizenship is a non-Muslim citizen in the practice of country life received unequal preferential treatment, and different treatment is based on religious differences. In contrast to the concept of modern Islamic citizenship that gives equal treatment to all citizens regardless of religion. The concept of citizenship by the Messenger of Allah (peace and blessings of Allaah be upon him) in the city of Madinah al munawarah is the best citizenship concept of all time. Rasulullah shollallahu 'alaihi wasallam gives examples of the concept of the best citizenship that there are values of divinity, humanity, democracy and justice. The doctrine of the concept of citizenship of the Messenger of Allah sallallaahu 'alaihi wasallam is the concept of citizenship kosmpolitan. Keywords: citizenship, dhimmi, rasulullah shollallahu 'alaihi wasallam, cosmopolitan ABSTRAK Konsep kewarganegaraan Islam terdapat dua, yaitu muslim dan dhimmi. Konsep kewarganegaraan dhimmi adalah warga negara non muslim dalam praktik kehidupan negara mendapat perlakuan istimewa yang tidak sama, dan perlakuan berbeda didasarkan karena perbedaan agama. Berbeda dengan konsep kewarganegaraan Islam modern yang memberikan perlakuan yang sama kepada semua warga tanpa membedakan agama. Konsep kewarga-negaraan yang diterapkan oleh Rasulullah shollallahu 'alaihi wasallam di kota Madinah al munawarah merupakan konsep kewarganegaraan yang terbaik sepanjang masa. Rasulullah shollallahu 'alaihi wasallam memberikan contoh konsep kewarganegaraan terbaik yang terdapat nilai-nilai ketuhanan, kemanusiaan, kerakyatan serta keadilan. Ajaran konsep kewarganegaraan Rasulullah shollallahu 'alaihi wasallam merupakan konsep kewargane-garaan kosmpolitan. Kata kunci: kewarganegaraan, dhimmi, Rasulullah shollallahu 'alaihi wasallam, kosmopolitan